Analiza statystyczna polsko-ukraińskiego interjęzyka – najtrudniejsze miejsca polskiej fleksji dla osób ukraińskojęzycznych - Izdebska-Długosz, Dominika (Przegląd Wschodnioeuropejski, 2023)
This paper presents part of a statistical analysis (SPSS) of the Polish-Ukrainian interlanguage which is currently being conducted. The presented part of the research pertains to the most difficult forms from the morphological level of the Polish language for speakers of Ukrainian who learn Polish as a foreign language, regardless of their declared level of language proficiency (A1+ ‒ B2+). The analyses presented in the article are of a qualitative nature. The questionnaire for the research into the interlanguage contained both correct and wrong forms (i.e. interferential forms extracted from the previous author’s corpus-based error analyses) – the respondent had to decide which form was correct. Therefore, the study concerns language intuition. The results of the research are convergent with the analyses of actual errors made by Ukrainians in their written assignments, which constitutes a motivation for further statistical analyses of the interlanguage with the use of the same research tool.